2017
DOI: 10.1002/glia.23249
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein 6 secreted by oligodendrocytes regulates the progression of experimental autoimmune encephalomyelitis

Abstract: Multiple sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system (CNS), and experimental autoimmune encephalomyelitis (EAE) is a well-established animal model of the disease. Here, we examined the pathophysiological role of Kallikrein 6 (Klk6), a serine protease produced by oligodendrocytes (OLs), in EAE using Klk6 knockout (Klk6-/-) mice. Compared with Klk6+/+ (wild-type) mice, Klk6-/- mice showed milder EAE symptoms, including delayed onset and milder paralysis. Loss of Klk6 sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 71 publications
1
54
0
2
Order By: Relevance
“…It is known that suppression of KLK6 reduces the expression levels of inflammatory cytokines, chemokines, and their receptors. 52 Interestingly, these oligodendrocyte-only related genes are in module 36, which is significantly changed by DTMP back to the naı¨ve expression pattern. The expression of these genes is significantly reversed towards the naı¨ve state with recoveries larger than 80%.…”
Section: Modulementioning
confidence: 97%
“…It is known that suppression of KLK6 reduces the expression levels of inflammatory cytokines, chemokines, and their receptors. 52 Interestingly, these oligodendrocyte-only related genes are in module 36, which is significantly changed by DTMP back to the naı¨ve expression pattern. The expression of these genes is significantly reversed towards the naı¨ve state with recoveries larger than 80%.…”
Section: Modulementioning
confidence: 97%
“…Of mature oligodendrocytes, the spinal cord-enriched MOL3, expressing the serine protease Klk6 was the most distinct. Klk6 was recently implicated in the pathogenesis of experimental autoimmune encephalomyelitis, a model of multiple sclerosis in mice (Bando et al, 2018).…”
Section: Loss Of Patterning In the Oligodendrocyte Lineage And Convementioning
confidence: 99%
“…These data underlie KLK6 as an attractive target for novel molecules that could inhibit its proteolytic activity as a treatment for various cancers (32)(33)(34). Finally, numerous studies indicated that KLK6 may also be involved in the pathogenesis of various neurodegenerative diseases, including Alzheimer's disease, Parkinson's disease, multiple sclerosis, and others (35)(36)(37)(38)(39)(40)(41). For example, raising neutralizing KLK6 antibodies in mice exerted overall beneficial effects in models of multiple sclerosis and CNS inflammatory disease, suggesting that selectively inhibiting KLK6 is not expected to be considerably toxic.…”
Section: Introductionmentioning
confidence: 98%